Psychometric Characteristics of Spanish Monosyllabic, Bisyllabic, and Trisyllabic Words for Use in Word-Recognition Protocols - Carlo, Mitzarie A.; Wilson, Richard H.; Villanueva-Reyes, Albert (Journal of the American Academy of Audiology, 2020)
Background English materials for speech audiometry are well established. In Spanish, speech-recognition materials are not standardized with monosyllables, bisyllables, and trisyllables used in word-recognition protocols.Purpose This study aimed to establish the psychometric characteristics of common Spanish monosyllabic, bisyllabic, and trisyllabic words for potential use in word-recognition procedures.Research Design Prospective descriptive study.Study Sample Eighteen adult Puerto Ricans (M = 25.6 years) with normal hearing [M = 7.8-dB hearing level (HL) pure-tone average] were recruited for two experiments.Data Collection and Analyses A digital recording of 575 Spanish words was created (139 monosyllables, 359 bisyllables, and 77 trisyllables), incorporating materials from a variety of Spanish word-recognition lists. Experiment 1 (n = 6) used 25 randomly selected words from each of the three syllabic categories to estimate the presentation level ranges needed to obtain recognition performances over the 10 to 90% range. In Experiment 2 (n = 12) the 575 words were presented over five 1-hour sessions using presentation levels from 0- to 30-dB HL in 5-dB steps (monosyllables), 0- to 25-dB HL in 5-dB steps (bisyllables), and −3- to 17-dB HL in 4-dB steps (trisyllables). The presentation order of both the words and the presentation levels were randomized for each listener. The functions for each listener and each word were fit with polynomial equations from which the 50% points and slopes at the 50% point were calculated.Results The mean 50% points and slopes at 50% were 8.9-dB HL, 4.0%/dB (monosyllables), 6.9-dB HL, 5.1%/dB (bisyllables), and 1.4-dB HL, 6.3%/dB (trisyllables). The Kruskal–Wallis test with Mann–Whitney U post-hoc analysis indicated that the mean 50% points and slopes at the 50% points of the individual word functions were significantly different among the syllabic categories. Although significant differences were observed among the syllabic categories, substantial overlap was noted in the individual word functions, indicating that the psychometric characteristics of the words were not dictated exclusively by the syllabic number. Influences associated with word difficulty, word familiarity, singular and plural form words, phonetic stress patterns, and gender word patterns also were evaluated.Conclusion The main finding was the direct relation between the number of syllables in a word and word-recognition performance. In general, words with more syllables were more easily recognized; there were, however, exceptions. The current data from young adults with normal hearing established the psychometric characteristics of the 575 Spanish words on which the formulation of word lists for both threshold and suprathreshold measures of word-recognition abilities in quiet and in noise and other word-recognition protocols can be based.
Keywords: auditory perception; normal hearing for pure tones; Spanish word recognition; speech perception; word recognition